Impact of laminae on pore structures of lacustrine shales in the southern Songliao Basin, NE China - Liu, Dongdong; Li, Zhuo; Jiang, Zhenxue; Zhang, Chen; Zhang, Ziya; Wang, Jianbo; Yang, Dongxu; Song, Yan; Luo, Qun (Journal of Asian earth sciences, 2019)
[Display omitted] •Laminated shales show greater variations in micropore volumes than massive shales.•Laminated shales have lower mesopore volumes than massive shales.•Laminated shales have more slit-like pores and fewer plate-like and ink-bottle pores than massive shales.•The pore structures of laminated shales are mainly influenced by TOC and Ro. Evaluating the influences of laminae on shale pore structures is vital to understand the enrichment mechanism of lacustrine shale gas. This study investigates lacustrine shales from the lower Cretaceous Shahezi Formation in the Changling Sag, southern Songliao Basin, NE China, using mineralogical and geochemical analyses, CO2 & N2 adsorption, and high-pressure mercury intrusion porosimetry (MIP), to compare pore structure characteristics between laminated and massive shales, and elucidate their main controlling factors. Our results show that, laminae in lacustrine shales from the Shahezi Formation include those clay-rich, organic-rich, and silty ones, and minor carbonate-rich ones. Micropores in both laminated and massive shales show tri-modal distributions with main peaks at 0.47–0.54 nm, 0.57–0.63 nm, and 0.80–0.85 nm, respectively; however, the laminated shales exhibit great variations in micropore volumes among different samples. Mesopores within the laminated shales are smaller than those in the massive shales, and their pore volumes (PV) are about 1/3 less than those of the massive shales. This is due to that the laminated shales are rich in slit-like pores whereas the massive shales have more plate-like and ink-bottle pores. Thermal maturity (Ro) and total organic carbon (TOC) contents are the essential factors controlling the development of micropores and mesopores in the laminated shales, however they show weak effects on macropore development in this formation; this may be related to that shales from the Shahezi Formation generally have low TOC contents and type III kerogen. Clay minerals and quartz both have weak relevance to pore development in this formation.